Population and distribution pattern of Poropuntius tawarensis in Lake Laut Tawar, Central Aceh Regency - Mufti Aulia Rahman; Abdullah Abdullah; Safrida Safrida; Muhammad Ali Sarong; Haekal Azief Haridhi (Faculty of Marine and Fisheries, Universitas Syiah Kuala, 2024)
Poropuntius tawarensis is an endemic fish of Laut Tawar that is currently classified as Endangered according to the IUCN Red List. The decline in its population is caused by habitat degradation, overfishing, and the introduction of alien species that act as predators This study aims to analyze the diversity and distribution patterns the population of kawan fish (Poropuntius tawarensis) in Lake Laut Tawar, Central Aceh Regency. Fish samples were collected from four different locations and analyzed using the Shannon-Wiener and Morisita indices. The results indicate that the diversity level of kawan fish (Poropuntius tawarensis) is classified as a